Survivin expression, HPV positivity and microvessel density in oropharyngeal carcinomas and relationship with survival time - Tastekin, Ebru (Arch Med Sci, 2016)
INTRODUCTION: Among head and neck cancers, those of the oral cavity and oropharynx are the second most prevalent following the larynx. This study aimed to research immunohistochemical expression of survivin, HPV positivity and microvessel density in tumors and their relationships with prognosis. MATERIAL AND METHODS: Pathological materials and demographic properties of 46 patients were retrospectively evaluated. Survivin, HPV and CD34 (for microvessel density evaluation) antibodies were applied tumoral tissues. Survival times, clinical stage and differentiation were evaluated. RESULTS: In univariate analysis, we observed that survivin, microvessel density and stage were significantly associated with survival time (p < 0.05). In multivariate analysis, only survivin and microvessel density were associated with survival time (p < 0.05). But we did not find significant correlation between neither tumor differentiation nor HPV positivity and survival (p > 0.05). CONCLUSIONS: Survivin levels and microvessel density were found to be effective prognostic factors and were related to survival in oral cavity and oropharyngeal cancers. Treatments targeting survivin expression and angiogenesis might be employed against these tumor groups.